ANCAMAN PERGESERAN BAHASA DAERAH DALAM ERA GLOBALISASI: TINJAUAN KASUS DI KABUPATEN BARRU - Inriani Rani; Arief Fiddienika (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2024)
This study aims to describe the threat of language shift occurring among the youth in Barru regency in the era of globalization. the method used is a qualitative approach that combines observation and interviews to explore changes in the use of the Bugis language among the youth in Barru Regency amid the currents of globalization. the data analysis method employed is thematic analysis, where patterns and themes emerging from the observation and interview data will be identified and analyzed. Respondents were deliberately selected, each aged 16, 19, and 21 years old, from Barru Regency. This selection aims to provide a better depiction of age variation within the studied population. The results of the study indicate that the youth in Barru Regency predominantly use the regional language in their daily interactions; however, there is a shift when interacting on social media, where Indonesian or trendy social media languages are more dominant. they also tend to perceive the regional language as less interesting and modern compared to more commonly used languages, such as Indonesian or foreign languages. additionally, the use of foreign words within the regional language has become a trend among the youth in Barru Regency. these findings highlight the influence of social media in altering language preferences and demonstrate the challenges in maintaining the sustainability of regional language usage in the era of globalization.